PENGARUH RETURN ON ASSETS (ROA), RETURN ON EQUITY (ROE), NET PROFIT MARGIN (NPM), dan EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM - Novia Kasyaretta Ananda Putri; Saryadi Saryadi (Universitas Diponegoro, 2017)
Share price is a form of public trust in the company's performance. This research uses fundamental analysis with financial ratio analysis. The Sub Residence Property Sector that has studied in the research consisted of 15 companies. In the last three years the average share price of sub-property property sector in the period 2014-2016 has increased but only one company of 15 companies that experienced an increase in share price each year. While other companies experiencing a fluctuating condition. This is the main reason why researchers do the research internally. This type of research is explanatory research, with population that can be researched in property sub residence sector are 15 companies. The type of data source is the secondary data, which obtained indirectly. The type of data used in this study is time series data. Data analysis methods used is classical assumption test, correlation, determination, simple regression, multiple regression, and significance by using SPSS application. The result of research stated that ROA, ROE and EPS have influence to stock price, which means when ROA, ROE and EPS increase, then stock price will partially increase. While NPM has no effect on stock prices. Simultaneous tests show ROA, ROE, NPM, and EPS have an influence on stock prices. If ROA, ROE, NPM, and EPS increase, then stock price will increase. Based on the results, researcher suggests that the subprojects subproperty must maintain their financial performance which includes ROA, ROE, NPM, and EPS to increase their stock price.